Students' Self-Assessment in Writing Class - Benny Krisbiantoro; Muhammad Soali; Anggit Wirasto (LPPM Universitas Harapan Bangsa, 2022)
The educational literature has devoted considerable focus to the pedagogical utility of rubrics in encouraging student learning and facilitating instructor feedback on student performance. However, there is little study on students' usage of self-assessment criteria in a context including a second or foreign language, and even less research has looked into the variables that affect the usefulness of the assessment criteria. The study aimed to investigate (1) how students perceive the rubric's function in evaluating their writing skills.; (2) according to the students, what factors affected the rubric's effectiveness for self-evaluation in the writing class? Forty students of the tenth grade of SMK Kesatrian Purwokerto got involved in this study. The researchers employed a self-assessment rubric and students’ reflective journals to collect the data. The findings of this study were that by helping students to set goals, make plans, keep an eye on themselves, and do reflection, rubrics were beneficial in fostering students' self-learning in writing skills. Rubric factors and users impacted the efficiency of the rubric for learner self-evaluation.